Pengembangan Media Pembelajaran Video Tutorial Pada Materi Rias Wajah Panggung Kelas XI SMK Negeri 6 Surabaya - Aisa Nur Layli; Maspiyah; Mutimmatul Faidah; Biyan Yesi Wilujeng (Program Studi Pendidikan Tata Rias, 2025)
The purpose of this project is to produce a video lesson that will function as an instructional tool for stage makeup in SMK Negeri 6 Surabaya's class XI. The five steps of the ADDIE development model—analysis, design, development, implementation, and evaluation—are used in this study's research and development. Expert validation for media elements was 96.88%, material aspects were 96.25%, and language aspects were 95%, according to the study's findings. With an overall average of 96.04%, it falls into the